Do You Really Love Me? - Cole, Alastair (UK ; France ; Republic of Macedonia ; Serbia ; Slovenia ; Italy ; Hungary : Nisi Masa : Tongue Tied Films, 2011)
The film follows six couples from across Southern Europe into their worlds of language and love, told in both their words and those of Scottish psychiatrist and poet, R.D Laing.
Verzio Film Festival Submission
Keywords: Documentary films